Universities with standards but not standard universities: students and academics reflection of university operating standards in Tanzania - Yohana William (Springer, 2024)
Abstract Quality of teaching and learning in higher education is explained by the teaching and learning milieus through which academic staff and students interact. Subsequently, governments across the globe have been establishing standards that aim at improving the teaching and learning milieus in universities as part of the efforts to facilitate the provision of quality university education that address national and global needs and contexts simultaneously. This paper draws evidence from the quantitative data gauging the reflection and experiences of academic staff and students regarding the extent to which milieus for the provision of education in post-1995 universities reflect the goals of the standards established to govern the operation of universities in Tanzania. Overall, the study found dissatisfactions from both academic staff and students regarding the extent to which the teaching and learning milieus in post-1995 universities in Tanzania reflect the standards. This poor reflection may have negative impacts on the realisation of the goals the standards intend to achieve. The study therefore underscores the need for the government to plan, design and enforce the appropriate standards that would have notable impacts on the academic experiences of academic staff and students and subsequently provision of education for national and global needs.